More Time Spent with Clear Skin and No Itch with Upadacitinib versus Dupilumab for Atopic Dermatitis - Andrew Blauvelt; Kilian Eyerich; Alan D. Irvine; Marjolein de Bruin-Weller; Shawn G. Kwatra; Melinda Gooderham; Brian Kim; Brian M. Calimlim; Wan-Ju Lee; Eliza M. Raymundo; Yingyi Liu; Sarah Ofori; et al. (Adis, Springer Healthcare, 2024)
Abstract Introduction Atopic dermatitis (AD), with its hallmark symptoms of pruritus and skin lesions, often impairs patients' quality of life. We assessed time spent with clear/almost clear skin and no/minimal itch during upadacitinib treatment versus placebo or dupilumab among patients with moderate-to-severe AD. Methods This analysis consisted of a post hoc analysis of Measure Up 1 (NCT03569293), Measure Up 2 (NCT03607422), and Heads Up (NCT03738397). Measure Up 1 and 2 were replicate, randomized, double-blind, placebo-controlled phase 3 studies with patients randomized (1:1:1) to once-daily oral upadacitinib 15 mg, upadacitinib 30 mg, or placebo for 16 weeks. Heads Up was a head-to-head, randomized, double-blind, double-dummy, phase 3b study with patients randomized (1:1) to upadacitinib 30 mg or subcutaneous dupilumab 300 mg for 24 weeks. Skin clearance was assessed with the Eczema Area and Severity Index (EASI) at baseline, weeks 1, 2, and 4, and every 4 weeks thereafter. Itch was assessed using the Worst Pruritus Numerical Rating Scale (WP-NRS) daily over 16 weeks and every 2 weeks thereafter to week 24 in Heads Up. Results This analysis included 1683 patients in Measure Up 1 and 2 and 673 patients in Heads Up. Through 16 weeks in Measure Up 1 and 2, patients receiving upadacitinib spent 9.8-13.4 times as many days with an EASI 90 response and 7.0-10.3 times as many days with a WP-NRS 0/1 response versus placebo. In Heads Up, patients receiving upadacitinib spent 2.0 and 1.7 times as many days through 16 and 24 weeks, respectively, with an EASI 90 response versus dupilumab. Through 16 and 24 weeks, patients receiving upadacitinib spent 3.0 and 2.6 times as many days, respectively, with a WP-NRS 0/1 response versus dupilumab. Conclusions Patients with moderate-to-severe AD spent more time with clear/almost clear skin and no/minimal itch with upadacitinib versus placebo or dupilumab. Trial Registration ClinicalTrials.gov identifier, Measure Up 1 (NCT03569293), Measure Up 2 (NCT03607422), Heads Up (NCT03738397).